KOMPOSISI VEGETASI DI KAWASAN HUTAN LINDUNG BATUKARU (RTK.4 : Desa Gesing, Kec. Banjar - Buleleng dan Desa Bukit Catu, Kec. Baturiti - Tabanan) - Alit Gunadi, I Gusti (Bumi Lestari; Vol 6 No 1, 2012)
The purposes of the research are to know the composition, distribution, and dominant species of vegetation at Batukaru forest conservation area (RTK-4). This research used transect method done by systematic plot sampling. Five transects were made, that was the distance of 1 km each transect line. In each transect line there were 10 plots with the dictance of 100 m each plot. The result of the experiment found 33 kinds of higher plant to cover the field on Gesing village and 18 kinds on Bukit Catu village, with Podocarpus imbricatus Blume is the dominant species on the both villages, with each the important value index of 88,82 % and 99,47 % for the higher plant, so that species not stable yet. The lower vegetations that identificated on each location are 27 and 34 kinds of species Diversity Index on some level of plant growth at Gesing and Bukit Catu villages are around 1,88 (sedling) – 2,77 (tree) and 1,77 (sedling) – 2,11 (tree), so the community condition is in the term of stable.
Keywords: Podocarpus imbricatus Blume, protected area, vegetation analysis